History of Raton's Memorial Library - Lloyd, Betty (New Mexico Libraries Newslettr, 1975)
The Arthur Johnson Memorial Library, formerly the Raton Public Library, was opened in Raton in 1912.Dr. J J. Shuler, a community minded citizen and Raton's first mayor, saw the need for a library.
Article about Raton's Memorial Library By Betty Lloyd in the New Mexico Libraries Newsletter located on page 3.
Master list item # 67
File location is in the Raton File Cabinet drawer 3
Keywords: Librarian -- Raton, New Mexico; Raton, New Mexico; Raton, New Mexico